Plasma Human Cartilage Glycoprotein‐39 and Cognitive Impairment After Acute Ischemic Stroke - Wang, Ziyi; Zhang, Kaixin; Zhong, Chongke; Zhu, Zhengbao; Zheng, Xiaowei; Yang, Pinni; Che, Bizhong; Lu, Yaling; Zhang, Yonghong; Xu, Tian (Journal of the American Heart Association, 2025)
Our study aimed at evaluating the association between plasma human cartilage glycoprotein-39 (YKL-40) and cognitive impairment at 3 months among patients with acute ischemic stroke. Plasma YKL-40 levels were measured in 604 participants from the China Antihypertensive Trial in Acute Ischemic Stroke. Cognitive impairment outcomes were assessed at 3 months poststroke using the Mini-Mental State Examination and the Montreal Cognitive Assessment. According to the Mini-Mental State Examination score, patients in the highest quartile of YKL-40 had a 2.01-fold (95% CI, 1.23-3.29; for trend=0.009) risk of poststroke cognitive impairment compared with those in the lowest quartile. Each 1 SD difference of logarithm-transformed YKL-40 was associated with a 28% (95% CI, 7-53) increased risk for the outcome. The multiple-adjusted spline regression model confirmed dose-response relationships between YKL-40 and poststroke cognitive impairment ( for linearity=0.01). Adding YKL-40 to a model containing conventional risk factors significantly improved the discriminatory power (area under the receiver operating characteristic curve improved by 0.02, =0.03). When cognitive impairment was defined using the Montreal Cognitive Assessment score, similar findings were observed. Elevated YKL-40 levels were associated with an increased risk of cognitive impairment at 3 months among patients with acute ischemic stroke. URL: clinicaltrials.gov; Unique Identifier: NCT01840072.